1991
DOI: 10.1515/hfsg.1991.45.s1.3
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Formation of Non-Cyclic Benzyl Ethers During Lignin Biosynthesis Part 3. The Reactivity of a β—O—4-Type Quinone Methide with Methyl-α-D-glucopyranoside in Competition with Vanillyl Alcohol. The Formation and the Stability of Benzyl Ethers between Lignin and Carbohydrates

Abstract: KeywordsLignin biosynthcsis Lignin modcl -O-4 Quinone mcthide LCC Methyl-a-D-glucopyranoside Phenols Alcohols J HNMR 13 C NMR 2-D NMR SummaryThe reactions of a -O-4-type quinone methidc with mcthyl-a-D-glucopyranosidc in the prescncc of vanillyl alcohol has bccn dctcrmincd in water-dioxane Solutions of diffcrcnt aciditics in ordcr to invcstigatc the formation of LCC during lignin biosynthesis. 1t was found that the carbohydratc could not compete with phcnols or watcr in reactions with the quinone mcthide neith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…A lignin-model study using a β- O -4-aryl ether QM compound, QM-GG (shown in Scheme ), was developed by Nakatsubo et al in 1976 . Since then, subsequent studies have been conducted for many purposes, such as studies on the reactivity of QMs toward different nucleophiles , and characterization of the syn - and anti -geometric isomers of 3-methoxy-substituted (G-type) QMs. ,, This β- O -4-aryl ether QM has been used to synthesize novel lignin model compounds for LCC linkages, dibenzodioxocin, and anthrahydroquinone adducts. , …”
Section: Resultsmentioning
confidence: 99%
“…A lignin-model study using a β- O -4-aryl ether QM compound, QM-GG (shown in Scheme ), was developed by Nakatsubo et al in 1976 . Since then, subsequent studies have been conducted for many purposes, such as studies on the reactivity of QMs toward different nucleophiles , and characterization of the syn - and anti -geometric isomers of 3-methoxy-substituted (G-type) QMs. ,, This β- O -4-aryl ether QM has been used to synthesize novel lignin model compounds for LCC linkages, dibenzodioxocin, and anthrahydroquinone adducts. , …”
Section: Resultsmentioning
confidence: 99%
“…They were previously assigned () to lignin−carbohydrate bonds of the benzyl−alkyl ether type according to data for model compounds (). Analysis of published data for various benzyl ether lignin−carbohydrate model compounds ( ) allows attribution of these signals to linkages between the α-position of lignin with primary hydroxyl groups of carbohydrates, such as those at C-6 in β- d -glucopyranosyl and α- d -galactopyranosyl and C-5 in α- l -arabinofuranosyl units. The CH-α moieties in benzyl ether linkages with secondary hydroxyl groups of carbohydrate give signals at a low proton field, at about δ C /δ H 80−82/4.9−5.25 ( , ), which were not detected in the spectra of the lignin investigated.…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29][30][31][32]. Although the HMQC spectra are not quantitative, they were obtained under the same conditions, that is, sample concentration, acquisition, and processing parameters.…”
mentioning
confidence: 99%
“…Therefore, the 4-O-methyl-glucuronic acid residue ester bonds are formed exclusively at the αposition of phenyl propane units. An acidic pH favours the reaction of quinone methide with glucuronic acid 46 . Biosynthesis of secondary cell walls starts by forming cellulose and hemicelluloses.…”
Section: Discussionmentioning
confidence: 99%